2003
DOI: 10.1097/00001756-200311140-00008
|View full text |Cite
|
Sign up to set email alerts
|

Cortical sound processing in children with autism disorder: an MEG investigation

Abstract: Previous work investigating frequency encoding mechanisms in human auditory cortex has provided evidence that latency of the auditory evoked M100 is strongly proportional to frequency, with low frequency (100^200 Hz) tones associated with B30 ms longer latencies than mid-range frequency (1^2 kHz) tones. Motivated by pervasive speech and auditory perception de¢cits observed in autism spectrum disorder, we evaluated M100 frequency dependence in children with autism disorder and typically developing controls.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 18 publications
4
57
0
Order By: Relevance
“…Mean (± SEM) latency values for the left hemisphere were: TD = 120.7±1.5ms, children with ASD = 130.2±9.4ms, p=0.3; right hemisphere values were: TD = 117.4±3.4ms, children with ASD = 136.8±4.4ms, p<0.01 ( Figure 2c). Although present findings show a developmental trajectory of M100 latency that is not significantly different than that of typical development, the finding reported in our previous study of longer M100 latencies in ASD (Gage et al, 2003b) was replicated. Furthermore, in these small sample studies, differences in the clinical and behavioral scores of the children with autism certainly exist, precluding direct comparison between studies but motivating further studies.…”
Section: Developmental Trajectory Of M100 Latencysupporting
confidence: 68%
See 1 more Smart Citation
“…Mean (± SEM) latency values for the left hemisphere were: TD = 120.7±1.5ms, children with ASD = 130.2±9.4ms, p=0.3; right hemisphere values were: TD = 117.4±3.4ms, children with ASD = 136.8±4.4ms, p<0.01 ( Figure 2c). Although present findings show a developmental trajectory of M100 latency that is not significantly different than that of typical development, the finding reported in our previous study of longer M100 latencies in ASD (Gage et al, 2003b) was replicated. Furthermore, in these small sample studies, differences in the clinical and behavioral scores of the children with autism certainly exist, precluding direct comparison between studies but motivating further studies.…”
Section: Developmental Trajectory Of M100 Latencysupporting
confidence: 68%
“…This latency shift is delayed in children with autism (and essentially not evident in the right hemisphere) (Gage et al 2003b). Recent pilot work extended previous M100 latency findings, examining M100 latencies from each hemisphere in children with typical development and in children with an ASD using whole-head 275-channel MEG.…”
Section: Developmental Trajectory Of M100 Latencymentioning
confidence: 52%
“…Reports have indicated that the ASD population exhibits elevated rates of brain stem or peripheral hearing dysfunction [13][14][15][16][17][18][19][20] and abnormalities in AEF components (i.e., cortical dysfunction) [1][2][3][4][5][6][7][8][9][10][21][22][23][24][25]. Intriguingly, research has indicated that individuals with ASD may present with peripheral auditory asymmetry [13], which may distort the cortical bilateral synchronization of AEF components in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, MEG has emerged as an important investigatory tool in neurodevelopmental studies because MEG has advantages over other neuroimaging techniques for young children, including safety, fewer constraints and less environmental noise. Using MEG, many recent studies have observed aberrant brain activities in children with ASD [1][2][3][4][5][6][7][8][9][10][21][22][23][24][25][26][27][28][29] by investigating brain connectivity [26,[28][29][30] or atypical brain responses to auditory stimuli [1][2][3][4][5][6][7][8][9][10][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation